Emotion dysregulation, dissociation and body dissatisfaction mediate the relationship between trauma exposure and ED symptoms - L. Lev-Ari; A. Zohar; R. Bachner Melman (European Psychiatry, 2022)
Introduction The current study tests the relationship between eating disorder (ED) symptoms and trauma exposure. The mechanisms via which trauma is related to ED symptoms have not been sufficiently examined. This study examines the complex role of dissociation and emotional dysregulation in the context of trauma, BMI, ED symptoms and body dissatisfaction (BD).